Over a million students use our free study notes to help them with their homework
Recall that sin(x) = (eix-e-ix)/(2i) and we can rewrite the integrand as {(eix-e-ix)/(2i)}6Factor out {1/(2i)}6, which is -1/64, of the in...
Cos^2(x) + sin^2(x) = 1. Therefore Cos^2(x) = 1 - sin^2(x). So equation becomes 3Sin^2(x) + sin(x) + 8 = 9(1 - sin^2(x)). Then becomes 12sin^2(x) + sin(x) - 1This is quadratic equation, solved to (4sin(x)...
=(3x56)x55
A stationary point implies that the gradient at this point will be equal to 0, it is a turning point in the graph. So we need to find the value of X at which dy/dx = 0. [where dy/dx is the gradient.]So we...
Recall the identity ((cos x)^2+(sin x)^ 2=1). Rearrange the identity to give cos x in terms of sin x. Substitute this into the equation. Rearrange so all terms are on one side of the equation and factorie...
←
171
172
173
174
175
→
Internet Safety
Payment Security
Cyber
Essentials